Utilizing pistachio green hull extract to produce sugar-free muffins with antioxidant and antidiabetic potential - Amin Karimi; Amir pouya Ghandehari Yazdi; Mohsen Barzegar; Mohammad Rahmati; Nooshin Bazsefidpar; Arash Soltani; Seid Mahdi Jafari (Applied Food Research)
The current study aimed to produce sugar-free muffins containing pistachio green hull extract (PGHE) as a natural source of antioxidant and antidiabetic compounds. The effects of PGHE substitution (1, 2, and 4% w/w) on the total phenolic content, antioxidant activity (DPPH scavenging), inhibition of α-amylase and α-glucosidase activities, storage stability (peroxide value and TBA), physicochemical, and sensory properties of muffins were investigated. The antioxidant activity of samples containing 4 % PGHE, demonstrated a 22-fold increase compared to the control. Furthermore, muffins containing PGHE displayed higher oxidation stability over a 14-day storage period. PGHE could improve α-amylase and α-glucosidase inhibitory activities of muffins up to 7-fold and 2-fold, respectively. Texture analysis revealed that increasing the amount of PGHE decreased the hardness, gumminess, and chewiness of muffins. Incorporation of PGHE into samples had a significant effect on the color. The muffins containing 2 % PGHE had an overall acceptance that was not significantly different from the control.